(untitled) (Al-Aasar, 2025)
The Treaty of Hudaybiyyah is considered a pivotal moment in the foreign policy of the State of Madinah under the leadership of Prophet Muhammad (PBUH). This treaty not only demonstrated the strategic wisdom of the Prophet (PBUH) but also laid the foundation for the expansion of Islam through peaceful means. While Muslim scholars regard the treaty as a manifestation of diplomatic foresight and divine guidance, some Orientalist scholars, including Montgomery Watt, have raised objections, arguing that the treaty was merely a tactical maneuver rather than a genuine commitment to peace. This study critically examines the significance of the Treaty of Hudaybiyyah from both Islamic and Orientalist perspectives. It highlights the long-term impact of the treaty on Islamic governance, interfaith relations, and geopolitical stability. The research delves into primary Islamic sources and evaluates Montgomery Watt’s objections in light of historical evidence and scholarly discourse. By comparing Islamic and Orientalist viewpoints, this study aims to clarify misconceptions and offer a balanced understanding of the treaty’s role in the foreign policy of the State of Madinah. It underscores how the treaty facilitated the spread of Islam, promoted coexistence, and strategically positioned the Muslim community for future developments. The findings suggest that the Treaty of Hudaybiyyah was not only a diplomatic success but also a testament to the Prophet’s (PBUH) vision for a just and inclusive society.